Mecanismos de identificación y nexuación compleja en la dinámica textual - Estanislao Ramón Trives (Estudios de Lingüística, 1983)
In front of the hypothesis of the subsidiarity, commonly accorded to the mechanisms of identification of reference under the label of substitutes (across transformations or without them), this research —to be continued— claims the primary role of those mechanisms with reference to the dialogical and/or spatial-temporal frame, as well concerning the explicit lexical units as the only contextually memorizable or [0] lexical units. In fact, I believe the mechanisms of identification of reference are the sure runaway in the textlinguistic activity; the ineffability of the polysemantic system-meaning is dialogically semiotized in the concrete sense-frame of the course of the textual dynamics.